Schlafen family member 11 indicates favorable prognosis of patients with head and neck cancer following platinum-based chemoradiotherapy - Hamada, Seijiro; Kano, Satoshi; Murai, Junko; Suzuki, Takayoshi; Tsushima, Nayuta; Mizumachi, Takatsugu; Suzuki, Masanobu; Takashima, Tsuyoshi; Taniyama, Daiki; Sakamoto, Naoya; Fujioka, Yoichiro; Ohba, Yusuke; et al. (Frontiers in Oncology, 2023)
Recently, Schlafen family member 11 (SLFN11) has been reported to increase the sensitivity of cancer cells to DNA-damaging agents, including platinum derivatives; thus, SLFN11 may be a predictive biomarker for platinum-based chemoradiotherapy (CRT). In this study, we examined whether SLFN11 expression was associated with the therapeutic outcome of platinum-based CRT in head and neck squamous cell carcinoma (HNSCC). We performed immunohistochemical analyses for SLFN11 expression in 161 HNSCC tissues from patients who had been administered cisplatin-based CRT and examined the correlation between SLFN11 expression and progression-free survival (PFS). Additionally, SLFN11 expression was examined in 10 paired samples obtained before and after CRT in patients with local failure. Furthermore, in vitro experiments were performed using several HNSCC cell lines and isogenic SLFN11-knockout cells to assess the association between SLFN11 expression and drug sensitivity. PFS was found to be significantly better in the SLFN11-positive group than in the SLFN11-negative group among the 161 patients (5-year PFS: 78.8% vs. 52.8%, respectively, p < 0.001). Similar results were observed for the PFS at each primary site. The percentage of SLFN11 positivity was lower in tumor samples from patients with local failure after CRT than that in the corresponding primary tumors before CRT in 8 of 10 cases. Results of the in vitro assay demonstrated that SLFN11-knockout cells exhibited reduced sensitivity to DNA-damaging agents but not to the non-DNA-damaging agent docetaxel. Our findings suggest that SLFN11 may serve as a potential biomarker for predicting the response of HNSCC patients to platinum-based CRT.